Zbiór Wiadomości do Antropologii Muzealnej (Polskie Towarzystwo Ludoznawcze, 2014)
Aspires to initiate debates and serve as a forum for discussion about museums as a cultural phenomenon especially taking into consideration contemporary ethnographic museum sector. Anthropological debates about museums as a cultural phenomenon applying methodology used in ethnology and cultural anthropology to explore the subject of museums, their objects and employees.
Keywords: Museums : Periodicals; Museums